Field notes contributed by Bill F. Huser, fall 1991 - Huser, Bill F.et al (1991)
List of birds and locations contributed by Bill F. Huser with observer Bob Livermore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed